THE TRADITION OF SARAKALAN AS A PREACHING MEDIUM IN TANJUNG BUGIS VILLAGE, SAMBAS DISTRICT, SAMBAS REGENCY - Malini (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The tradition of sarakalan at weddings is called art or tradition as a place for preaching. The tradition of sarakalan or the reading of the Barzanji book accompanied at every wedding event by Malay people who are synonymous with Muslims, is one of the routine rituals that is still preserved to this day in Sambas Regency. The reading of Assalai/Asyraqal is known to the Sambas Malay community by many terms, and is often also known as sarakalan/nyerakal at weddings. This tradition is a real form of cultural ritual tradition with a religious nuance that has survived to this day, especially in Sambas Regency. This type of research is a qualitative research method with a descriptive approach. The data sources used are primary data and secondary data. Data collection techniques used were interviews, observation and documentation. The analysis technique is carried out by reducing data, presenting data and drawing conclusions. Data validity checking techniques are carried out by means of triangulation, member checking and verification or conclusions. The results of the research show: First, the implementation of the sarakalan tradition in Tanjung Bugis village, Sambas District, Sambas Regency, is the first event is an opening guided by the host or MC, the second event is a welcoming speech from the host, the third event is sarakalan (reciting Assalai, Rawi and Asyraqal ) and reading prayers, then the fourth event continued, namely speeches from representatives of invited guests, the fifth event was serving dishes and the last event was the closing of the event. Second, the function of the sarakalan tradition as a media for da'wah in Tanjung Bugis village, Sambas District, Sambas Regency is as an entertainment media, da'wah media and educational media. Third, the supporting and inhibiting factors for implementing the sarakalan tradition as a medium for da'wah in Tanjung Bugis village, Sambas District, Sambas Regency are the supporting factors, support from the village, enthusiasm from the participants in carrying out the activity, thus making invited guests enthusiastic about attending the event. The inhibiting factors are the lack of costs, lack of public interest in joining the sarakalan.